Sequentially fermented dealcoholized apple juice intervenes fatty liver induced by high-fat diets via modulation of intestinal flora and gene pathways. (June 2022) - Li, Hongcai; Liang, Jingjing; Han, Mengzhen; Wang, Xingnan; Ren, Yichen; Wang, Yaqin; Huang, Jintao; Li, Shiqi; Liu, Caiyun; Wang, Zhouli; Yue, Tianli; Gao, Zhenpeng
Graphical abstract: Highlights: S. cerevisiae and L. plantarum sequentially fermented dealcoholized apple juice has the effect of reducing fat and regulating fatty liver. Long-term consumption of low-alcohol cider under high-fat diet can aggravate fatty liver and inflammation of the body. S. cerevisiae and L. plantarum sequentially fermented dealcoholized apple juice reduce inflammation by regulating the LPS/LBP/CD14/TLR4 signaling pathway. Genes MBOAT7, TMC4, CYP2E1 and CYP7A1 have potential mechanisms for lipid accumulation and fatty liver regulation. S. cerevisiae and L. plantarum sequentially fermented dealcoholized apple juice enrich the gut microbial abundance and short-chain fatty acid content. Abstract: Low-alcohol beverages damage the liver, whereas dealcoholized apple juice sequentially fermented by Saccharomyces cerevisiae and Lactobacillus plantarum is a promising dietary intervention for hyperlipidaemia as a functional non-alcoholic beverage that lowers lipid levels and regulates fatty liver. However, their mechanisms of action have not been identified. In this study, we found that low-alcohol cider exacerbated inflammation in mice on a high-fat diet, up-regulate fatty liver CYP2E1 gene, and inhibit the expression of MBOAT7 and TMC4 . Apple juice traditionally fermented by S. cerevisiae and then dealcoholized, followed by sequential fermentation by L. plantarum, can improve obesity and fatty liver, reduce the production of liver cholesterol and fat accumulation, and promote the production of short-chain fatty acids. Our research demonstrates that the lipopolysaccharide/lipopolysaccharide-binding protein/cluster of differentiation 14 protein/Toll-like receptor 4 protein signaling pathway affects the occurrence of obesity and inflammation in mice, and the expression of CYP7A1 inhibits the production of lipids. Further research reveals that L. plantarum sequentially fermented dealcoholized apple juice not only regulate and restore the intestinal flora, but also change the ratio of Firmicutes -to- Bacteroides, and decreased endotoxin-bearing Proteobacteria levels. Together, this functional product may be a potential dietary strategy to interfere with hyperlipidemia and obesity-related metabolic disorders.